Procedure for Issuing Cement Unloading Documents at PT. PBM Gelora Perkasa Belawan - Muhammad Rizky; Dina Rispianti (UNIVERSITAS MARITIM AMNI SEMARANG, 2024)
This paper was written to find out more clearly how the Cement Unloading Document Issuance Procedure is at PT. PBM Gelora Perkasa Belawan. The goal to be achieved is to find out how PBM carries out the cement unloading document issuance procedure at the Belawan Main Harbor Master's office. Before issuing the Cement Unloading document, PBM must make preparations before the ship arrives, namely PBM must prepare several documents. Then this research was carried out at PT. PBM Gelora Perkasa Belawan, while the author was carrying out land practice from January 2024 to July 2024. The data source is directly from the research location by means of observation, as well as regulations related to the paper. The results obtained regarding the cement unloading document issuance procedure have been running optimally, but there are obstacles in the unloading document issuance procedure. The obstacles faced in the cement unloading document issuance process are system errors that occur due to poor network, resulting in inefficient time to issue cement unloading documents. The methods used by the author in completing this paper are Library Research and Field Research to make it easier for the author to complete this paper.